The Ethical Management Practices of Australian Firms - Batten, Jonathan (Journal of business ethics, 1997)
This paper addresses a number of important issues regarding the ethical practices and recent behaviour of large Australian firms in nine industries. These issues include whether firms have a written code of ethics, whether firms have a forum for the discussion of ethics, whether managers consider that their firm's activities have an environmental impact and whether there are any statistical relationships between the size, industry class, ownership, international involvement and location of the firm and its ethical management practices. These questions are examined by using data collected from a sample of 136 large firms operating in Australia.